2017
DOI: 10.1108/ecam-09-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of factors causing cost overruns and time delays in large public construction projects

Abstract: Purpose The purpose of this paper is to explore the impact that cost overruns and time delays exert on large public construction projects to clarify how past and current research regard factors causing cost overruns and time delays in large public construction projects. Design/methodology/approach This paper, which is based on an analysis of a literature selection consisting of 40 journal articles, investigates and ranks the occurrence of and the explanations for cost overruns and time delays in large public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 26 publications
2
96
0
4
Order By: Relevance
“…• Digital design communication tools: Digital Twin, Building Information Systems (BIM) including Revit, ArchiCAD, Navisworks, BIMx, BricsCAD, Archibus, Constructor, IntelliCAD, VisualARQ, Revizto; Geographic Information Systems (GIS) including QGIS, ArcGIS, and ArcMap [17]. The literature frequently reports that design mistakes, errors, changing orders and scopes, later approvals, and late technical decision makings were the main causes of delay in different contexts [95,99,104]. • Digital communication systems: cloud-based tools, emails, smart phones, and radio communication systems.…”
Section: Discussion and The Dec Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…• Digital design communication tools: Digital Twin, Building Information Systems (BIM) including Revit, ArchiCAD, Navisworks, BIMx, BricsCAD, Archibus, Constructor, IntelliCAD, VisualARQ, Revizto; Geographic Information Systems (GIS) including QGIS, ArcGIS, and ArcMap [17]. The literature frequently reports that design mistakes, errors, changing orders and scopes, later approvals, and late technical decision makings were the main causes of delay in different contexts [95,99,104]. • Digital communication systems: cloud-based tools, emails, smart phones, and radio communication systems.…”
Section: Discussion and The Dec Conceptual Modelmentioning
confidence: 99%
“…• Digital communication systems: cloud-based tools, emails, smart phones, and radio communication systems. Some studies report that the communication and the coordination between different parties were poor [27,95,96,99,109].…”
Section: Discussion and The Dec Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the studies in which the factors causing delay in construction were collected and identified from [35,50,3,34,36,51,37,52,32,53]. Furthermore, [5,33,14,38,39,54,38,40,41], were reviewed to collect the main and sub-factors of causing time overrun in construction projects. In general, in this review, an inclusive category on the causes of construction delay was identified after the detailed review of the published articles.…”
Section: Causes Of Delaymentioning
confidence: 99%
“…Many factors contribute to cost overruns, but poor cost estimation practices are a major influencing factor (e.g. Adam et al, 2017;Larsen et al, 2016). Aljohani et al (2017) point out that estimation methods used in practice are still affected by the estimator's bias and varying degrees of experience.…”
Section: Introductionmentioning
confidence: 99%